2022
DOI: 10.1128/jvi.00128-22
|View full text |Cite|
|
Sign up to set email alerts
|

Distinctive Roles of Furin and TMPRSS2 in SARS-CoV-2 Infectivity

Abstract: SARS-CoV-2, the etiological agent of COVID-19, has so far resulted in >6.1 million deaths worldwide. The spike protein (S) of the virus directs infection of the lungs and other tissues by binding the angiotensin-converting enzyme 2 (ACE2) receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(141 citation statements)
references
References 75 publications
4
120
0
2
Order By: Relevance
“…This conclusion was later supported by a large meta-analysis that suggested that statins significantly reduce the risk of adverse outcomes of COVID-19 [75]. While the convertase Furin plays a key role in SARS-CoV-2 infection by activating its spike glycoprotein [76], no association between plasma PCSK9 levels and the severity of COVID-19 infection and associated inflammation is yet available. Therefore, randomized clinical trials are urgently needed to establish the usefulness of routine combined use of statins and PCSK9 inhibitors in the treatment of SARS-CoV-2 or other coronavirus infections and their associated cardiovascular complications.…”
Section: Pcsk9 In Viral Infectionsmentioning
confidence: 99%
“…This conclusion was later supported by a large meta-analysis that suggested that statins significantly reduce the risk of adverse outcomes of COVID-19 [75]. While the convertase Furin plays a key role in SARS-CoV-2 infection by activating its spike glycoprotein [76], no association between plasma PCSK9 levels and the severity of COVID-19 infection and associated inflammation is yet available. Therefore, randomized clinical trials are urgently needed to establish the usefulness of routine combined use of statins and PCSK9 inhibitors in the treatment of SARS-CoV-2 or other coronavirus infections and their associated cardiovascular complications.…”
Section: Pcsk9 In Viral Infectionsmentioning
confidence: 99%
“…Viral entry is also dependent on the activity of cathepsin B/L which can be a substitute for TMPRSS. Then, virus recognition occurs when the S protein interacts with the membrane protease, which facilitates membrane fusion at the plasma membrane [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, any spike-specific CD4 T cells should be able to help B cells that are able to take up spike protein via specificity for RBD. However, spike protein is very large and is designed to be cleaved during viral entry into target cells, involving multiple proteases (52)(53)(54), so it is possible that spike available for B cell recognition in germinal centres may also be cleaved to smaller protein fragments, only some of which link B cell and T cell epitopes around RBD. Clearly this needs further study with defined epitopes, along with the clonal relationships between germinal centre Tfh cells during acute infection and memory cells during convalescence.…”
Section: Discussionmentioning
confidence: 99%